Study on Startup Performance of Flat-type of CPL Evaporator - 刘志春; 刘伟; 宰军; 邓芳芳 (Zhileng xuebao)
The startup process of CPL(Capillary pumped loop) was analyzed.Then a mathematical and physical model concerning CPL evaporator startup was established and the numerical method was applied to obtain the startup performance.A flat type CPL test-bed was designed and built.The results show that the numerical results agree well with the experimental data.In addition,the effects of different evaporator configurations on the startup characteristics were investigated and some methods and measures were discussed and presented to improve the startup performance and enhance the CPL operating stability.